Macrocycle-derived cobalt-nickel-loaded nitrogen-doped carbon catalyst as well as preparation method and application thereof

By preparing a macrocyclic-derived cobalt-nickel-loaded nitrogen-doped carbon catalyst CoNi@CN, the problems of large metal dissolution and low catalytic efficiency in carbon-based material catalysts were solved, and efficient removal of tetracycline antibiotics in water was achieved, while the stability and environmental safety of the catalyst were improved.

CN120733774APending Publication Date: 2025-10-03NANJING INST OF ENVIRONMENTAL SCI MINIST OF ECOLOGY & ENVIRONMENT OF THE PEOPLES REPUBLIC OF CHINA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510950322.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-10
Publication Date
2025-10-03

AI Technical Summary

Technical Problem

Existing carbon-based catalysts have large metal dissolution and low catalytic efficiency when activating peroxymonosulfate, and may cause environmental pollution and equipment corrosion, making it difficult to effectively remove difficult-to-degrade organic pollutants such as tetracycline.

Method used

The seven-membered cucurbitacin ring CB[7] was used as a carbon source and mixed with cobalt salt and nickel salt by stirring at room temperature to prepare a macrocyclic-derived cobalt-nickel-supported nitrogen-doped carbon catalyst CoNi@CN, which was used to activate peroxymonosulfate to form CoNi metal clusters, inhibit metal dissolution and improve electron transfer efficiency.

Benefits of technology

It improves the catalytic activity of the oxidant PMS, reduces the amount of metal dissolution, avoids environmental pollution, and improves the stability of the catalyst and the efficiency of electron transfer. It is suitable for the removal of refractory organic matter, especially tetracycline antibiotics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120733774A_ABST
    Figure CN120733774A_ABST
Patent Text Reader

Abstract

The invention discloses a macrocycle-derived cobalt-nickel-loaded nitrogen-doped carbon catalyst and a preparation method and application thereof, the catalyst is CoNi-CN, and the catalyst is prepared by calcining CB [7] / CoNi of a complex obtained by cucurbit [7] uril (CB [7]), cobalt salt and nickel salt at 500-900 DEG C in a protective atmosphere. The catalyst can effectively inhibit aggregation of cobalt and nickel metals. The CoNi-CN catalyst can be used for efficiently activating peroxymonosulfate and effectively removing antibiotics and anti-inflammatory drugs such as tetracycline, sulfamethoxazole and ciprofloxacin, is less in metal dissolution and high in removal efficiency, can be used for purifying organic matters, and has an application value of treating refractory organic matters, such as emergency treatment of water bodies polluted by the antibiotics and the anti-inflammatory drugs.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of water pollution control, and specifically relates to a macrocyclic-derived cobalt-nickel-supported nitrogen-doped carbon catalyst (CoNi@CN) and a preparation method and application thereof. Background Art

[0002] With the rapid development of society, the adverse impact of organic pollutants on the environment has become increasingly severe. Among them, antibiotics as a new type of organic pollutants have attracted great attention.

[0003] Tetracycline antibiotics (TCs) are widely used in medicine and aquaculture. They are used in significant quantities in today's production and daily life, and their release into the environment is significant. However, tetracyclines are known to be stable and difficult to biodegrade. Traditional wastewater treatment methods, including physical and chemical methods, activated sludge methods, and biofilm methods, primarily aim to remove biodegradable organic matter (BOD5 / COD > 0.3), ammonia nitrogen, total nitrogen, total phosphorus, and suspended solids. However, these physical, chemical, and biodegradation processes have low antibiotic removal rates. Consequently, tetracyclines, once released into the environment, are prone to accumulation along the food chain, posing a serious threat to human health.

[0004] As an efficient method for removing organic pollutants, advanced oxidation technology has been widely used in the removal of antibiotics in water. Among them, the advanced oxidation technology based on peroxymonosulfate (PMS) and peroxydisulfate (PS) has the advantages of strong stability, simple operation and no need for additional energy, and has been widely used in the field of organic pollutant removal in wastewater. The strong oxidizing ability of PMS or PS is based on the SO4 generated by its activation. ·− Activation pathways include UV activation, thermal activation, alkali activation, ultrasound activation, transition metal activation, and carbon-based material activation. Carbon-based materials are readily available, simple to prepare, have strong adsorption capacity, and do not cause secondary pollution to the environment, making them ideal heterogeneous catalytic materials.

[0005] Studies have shown that metal doping modification (such as the introduction of transition metals such as Fe, Co, and Ni) can significantly improve the electron transfer ability and free radical generation efficiency of carbon-based materials. However, the problem of metal dissolution has always been a key bottleneck restricting the engineering application of such catalysts. First, the loss of metal ions will destroy the skeleton structure of the catalyst, resulting in a reduction in active sites and a decrease in specific surface area, seriously affecting the stability and economy of the catalyst. Secondly, the dissolved metal has corrosive damage to process equipment, and its synergistic effect with the corrosive medium will accelerate the electrochemical corrosion of the reactor wall, directly increasing the equipment maintenance cost. Finally, the dissolved metal ions (Fe 3+ 、Co 2+etc.) are biologically toxic in themselves and can easily cause secondary pollution of soil or water, posing a potential ecological safety risk. Summary of the Invention

[0006] In view of the problems in the prior art of using carbon-based materials for catalyzing PMS, such as large metal dissolution, slow catalytic efficiency, and the need to add high concentrations of carbon-based materials or PMS to achieve efficient removal of organic pollutants, the present invention uses the seven-membered cucurbit ring CB[ 7 ] as a nitrogen-containing carbon source, a cobalt-nickel metal-doped complex was obtained as a precursor by a room temperature stirring method, and a new macrocyclic-derived cobalt-nickel-loaded nitrogen-doped carbon material (CoNi@CN) was prepared by a one-step pyrolysis method as a PMS catalyst for removing tetracycline from water. It can effectively improve the catalytic activity towards the oxidant PMS while significantly reducing metal dissolution, avoiding environmental risks.

[0007] The macrocycle-derived cobalt-nickel-loaded nitrogen-doped carbon material (CoNi@CN) of this invention achieves efficient activation of PMS through physicochemical synergy and exhibits excellent stability. As a novel heterogeneous catalyst, CoNi@CN effectively enhances electron transfer efficiency and active site density through metal-nitrogen-carbon synergy, providing a novel solution for addressing sudden incidents of recalcitrant organic contamination. This achievement not only expands the application scope of cucurbitacin-based functional materials but also provides theoretical support and technical reserves for the emergency treatment of persistent organic pollutants in drinking water safety systems.

[0008] To achieve the above object, the present invention adopts the following technical solutions: A method for preparing a macrocyclic-derived cobalt-nickel supported nitrogen-doped carbon catalyst comprises the following steps: (1) CB[ 7 ] (seven-membered cucurbit ring), cobalt salt and nickel salt are mixed and reacted in an organic solvent to obtain the complex CB[ 7 ] / CoNi; (2) The complex CB[ 7 ] / CoNi is calcined at 500-900°C under a protective atmosphere to obtain the macrocyclic-derived cobalt-nickel-supported nitrogen-doped carbon catalyst, which is denoted as CoNi@CN.

[0009] Preferably, the CB[ 7 ] (Seven-membered cucurbit ring) was prepared by the following method: Paraformaldehyde was slowly added to the concentrated hydrochloric acid solution of glycoluril until the solution became gel-like, and then refluxed at 100 °C for 24 h. After the reaction was complete, acetone was added to make CB[ 7 ]precipitate and you will get it.

[0010] Preferably, the glycoluril is prepared by the following method: Concentrated sulfuric acid is added to the aqueous solution of urea, followed by slow addition of glyoxal at 50°C, followed by heating to 85°C for 2 hours. After the reaction is complete, the pH is adjusted to 7, and the resulting solid is glycoluril.

[0011] Preferably, in the cobalt salt and the nickel salt in step (1), the molar ratio of cobalt element to nickel element is 2:1 to 1:3, more preferably 1:1.

[0012] Preferably, the cobalt salt in step (1) is cobalt acetate, and the nickel salt is nickel sulfate.

[0013] Preferably, the organic solvent in step (1) is anhydrous methanol.

[0014] Preferably, step (1) further comprises washing and drying the complex CB[ 7 More preferably, the washing is performed by washing with ethanol and water respectively.

[0015] Preferably, the calcination time in step (2) is 2 to 5 hours, more preferably 2 hours.

[0016] Preferably, the heating rate of calcination in step (2) is 5-20°C / min, more preferably 5°C / min.

[0017] Preferably, the protective atmosphere in step (2) is N2 atmosphere.

[0018] Preferably, the calcination in step (2) is carried out in a tube furnace.

[0019] The present invention also provides a macrocyclic-derived cobalt-nickel-supported nitrogen-doped carbon catalyst prepared by the above preparation method.

[0020] The present invention also provides the use of the macrocyclic-derived cobalt-nickel-supported nitrogen-doped carbon catalyst prepared by the above preparation method in degrading organic pollutants in water.

[0021] Preferably, the organic pollutant is tetracycline (TCH), the anti-inflammatory and antibacterial drug sulfamethoxazole (SMX) or ciprofloxacin (CIP).

[0022] Preferably, the application comprises the following steps: Peroxymonosulfate (PMS) is added to the water to be treated, and then the macrocyclic-derived cobalt-nickel-supported nitrogen-doped carbon catalyst is added to the water to be treated so that the final concentration of the macrocyclic-derived cobalt-nickel-supported nitrogen-doped carbon catalyst is 0.01 to 0.2 g / L, more preferably 0.05 g / L.

[0023] Preferably, before adding the cobalt-nickel-supported nitrogen-doped carbon catalyst, the concentration of the peroxymonosulfate in the water to be treated is 0.1-1.2 mM.

[0024] The beneficial effects of the present invention are: (1) Cucurbituril (CB[7]) has a unique three-dimensional cyclic molecular structure, host-guest recognition properties and excellent thermal stability. The molecular cavity formed by its cyclic structure can selectively encapsulate metal ions, which helps to reduce the metal dissolution rate of the material during the catalytic process and inhibit the agglomeration of metal particles. The present invention uses CB[7] as a supramolecular template to spatially regulate the bimetallic (Co-Ni) coordination, forming obvious CoNi metal clusters (5~10 nm), effectively inhibiting the aggregation of transition metals in the modified carbon-based material, and the obtained CoNi@CN has excellent catalytic activity and stability.

[0025] (2) The CoNi@CN of the present invention has low metal dissolution in water and will not cause secondary pollution to water when actually used for pollutant degradation.

[0026] (3) The CoNi@CN of the present invention increases the reaction rate of the oxidant PMS in degrading pollutants, while reducing the amount of catalyst added and the cost. In addition, the CoNi@CN catalyst has good stability, magnetic properties (saturation magnetization intensity = 2.96 emu / g), and is easy to operate.

[0027] (4) The CoNi@CN of the present invention can be used in combination with PMS to effectively remove pollutants such as sulfamethoxazole, organic pollutants nitrobenzene and p-chlorobenzoic acid from polluted water bodies with high removal efficiency. It can be used for the purification of organic matter and has application value in treating difficult-to-degrade organic matter, such as emergency treatment of water bodies contaminated by broad-spectrum fungicides or industrial organic raw materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 These are TEM-HAADF images of CoNi@CN and the reference product in Example 1 (6), where (a) is CoNi@CN and (b) is the reference product.

[0029] Figure 2 This is the SEM-EDS energy spectrum analysis result of CoNi@CN in Example 1 (7).

[0030] Figure 3 This is a graph showing the relationship between the removal rate of TCH and time in each group of simulated sewage in Example 2 (2).

[0031] Figure 4 This is a graph showing the relationship between the removal rate of TCH and time in each group of simulated sewage in Example 3 (3).

[0032] Figure 5 4 is a graph showing the relationship between the removal rate of TCH in each group of simulated sewage and time.

[0033] Figure 6 5 is a graph showing the relationship between the removal rate of TCH and time in each group of simulated sewage in Example 5.

[0034] Figure 7 4 is a graph showing the relationship between the removal rate of TCH and time in each group of simulated sewage in Example 6.

[0035] Figure 8 7 is a graph showing the relationship between the removal rate of TCH in each group of simulated sewage and time.

[0036] Figure 9 This is a graph showing the relationship between the removal rate and the number of recycling times when the CoNi@CN material, which has been regenerated and recovered 1-5 times, is used to activate PMS to remove TCH in water for 25 minutes.

[0037] Figure 10 This is the result of the magnetic detection experiment analysis on the CoNi@CN material in Example 8.

[0038] Figure 11 These are the XRD analysis results of the CoNi@CN material before and after use in Example 9.

[0039] Figure 12 This is the analysis result of the nitrogen isothermal adsorption-desorption experiment of the CoNi@CN material in Example 9.

[0040] Figure 13 This is the result of the experimental analysis of the detection of cobalt and nickel elements in simulated sewage in Example 10. DETAILED DESCRIPTION

[0041] This invention explores the mechanism and efficacy of a CoNi@CN-activated PMS system and attempts to apply it to the degradation of typical persistent organic pollutants, such as antibiotics. This research has important academic and application value for the development of PMS-based advanced oxidation processes and the efficient control of refractory organic pollutants in water. The invention is further described below in conjunction with the accompanying drawings and specific embodiments.

[0042] Example 1 (1) Urea (18 g, 0.3 mol) was dissolved in purified water (20 mL), and concentrated sulfuric acid (2 mL) was added. The mixture was stirred in an oil bath. 40% glyoxal (15.6 g) was slowly added dropwise at 50°C. The temperature was raised to 85°C and the reaction was continued for 2 h. The pH was adjusted to 7 with NaOH (0.1 M). The light yellow solid, the intermediate glycoluril, was filtered and dried in an oven at 60°C.

[0043] (2) Take 20 g of glycoluril, add concentrated hydrochloric acid (50 mL) and stir until it is completely dissolved. Continue stirring and slowly add paraformaldehyde (8.4 g) until the solution becomes gel-like. Heat the oil bath to 100 °C and reflux for 24 h. Cool naturally to room temperature to obtain a mixture solution. Then add acetone, cucurbituril [7] (CB[ 7 ]) precipitated, filtered and dried to obtain CB[ 7 ]solid.

[0044] (3) Take CB[ 7 ] (0.2240 g, 0.2 mmol), Co(Ac)2·4H2O (0.050 g, 0.2 mmol) and NiSO4·6H2O (0.053 g, 0.2 mmol) were added to the solution at a cobalt / nickel ratio of 1:1. The mixture was stirred at room temperature for 24 hours in anhydrous methanol (20 mL). The mixed solution was filtered, and the resulting pale yellow solid was washed three times with ethanol and then water, respectively, and dried in an oven at 60°C to obtain the complex CoNi / CN.

[0045] (4) The ground complex CB[ 7 ] / CoNi was loaded into a porcelain boat, placed in a tube furnace, introduced with N2, heated to 700℃ at a rate of 5℃ / min, calcined for 2 h, and naturally cooled to obtain a black sample, which was washed three times with water and ethanol respectively, dried at 60℃, and ground to obtain the catalyst CoNi@CN.

[0046] (5) Directly use the glycoluril prepared in step (1) to replace CB[ 7 ], and prepare the reference substance in the same manner as steps (3) and (4).

[0047] (6) CoNi@CN and the reference were observed by scanning electron microscopy TEM-HAADF. Figure 1 As shown in the figure, the metal in the control sample aggregated into metal particles of 500 nm in size, while the metal in the CB[ 7 As a precursor of carbon and nitrogen, it can effectively inhibit metal agglomeration during the material preparation process. Large particles produced by metal agglomeration cover a large number of catalytic active sites, significantly weakening the material's catalytic activity.

[0048] (7) The CoNi@CN prepared in step (4) was subjected to elemental energy spectrum analysis. The results are as follows: Figure 2 As shown, the results show that Co, Ni, N, C, and O are uniformly distributed on the catalyst surface, indicating that there are a large number of co-dopant atoms within the nitrogen-doped porous carbon structure, which can provide sufficient active sites for the reaction.

[0049] Example 2 Application comparison: Degradation of tetracycline (TCH) in water by PMS alone, CoNi@CN alone, and CoNi@CN / PMS system: (1) Dissolve TCH in water to prepare multiple simulated wastewaters, and control the TCH concentration to be 20 μM.

[0050] (2) Prepare a PMS solution with a concentration of about 100 mM, add it to the simulated sewage of the PMS group alone and the CoNi@CN / PMS group, and stir to obtain a mixed solution with a PMS concentration of 0.75 mM. Add the CoNi@CN prepared in Example 1 to the simulated sewage of the CoNi@CN group alone and the CoNi@CN / PMS group to make its concentration in the solution about 0.05 g / L, control the reaction temperature to 25°C, take out a certain amount of sample at regular intervals and filter, and perform subsequent TCH concentration analysis on the filtrate. The removal effect is shown in FIG. Figure 3 shown.

[0051] Example 3 Effect of materials with different CoNi ratios on the degradation of tetracycline (TCH) in water by activating PMS: (1) The same as (1)-(4) of Example 1, except that the cobalt / nickel metal ratio was controlled to be 1:0 (i.e., no nickel added, denoted as Co@CN), 0:1 (i.e., no cobalt added, denoted as Ni@CN), 1:1, 1:2, 3:1, and 2:1, respectively, to prepare CoNi@CN catalysts with different CoNi ratios. Commercial Co3O4 was also used for comparison.

[0052] (2) Dissolve TCH in water to prepare multiple simulated wastewaters, controlling the TCH concentration to 20 μM. Add a PMS solution with a concentration of approximately 100 mM to each set of simulated wastewater and stir until the PMS concentration reaches 0.75 mM.

[0053] (3) Add each catalyst group in (1) to the simulated sewage to a concentration of about 0.05 g / L in the solution, start the reaction, and control the reaction temperature to 25°C. Take out a certain amount of sample at regular intervals and filter it. The filtrate is then analyzed for TCH concentration. Figure 4 shown.

[0054] As can be seen, with all other conditions remaining unchanged, the CoNi@CN material significantly improved the removal rate of TCH in water compared to the cobalt- or nickel-loaded materials alone. Within 25 minutes, the TCH removal rates of the Co@CN and Ni@CN activated PMS were only 77.1% and 55.5%, respectively. The CoNi@CN material, with a cobalt / nickel molar ratio of 1:1, showed the best TCH degradation, achieving a TCH removal rate of 99.6% within 25 minutes.

[0055] Example 4 Effects of CoNi@CN materials on removing typical organic pollutants from water by activating PMS under different PMS concentration gradients: TCH was dissolved in water to prepare multiple simulated sewage, and the TCH concentration was controlled to be 20 μM. A PMS solution with a concentration of about 100 mM was added to each group of simulated sewage and stirred to make the PMS concentrations of 0.25 mM, 0.50 mM, 0.75 mM, and 1.00 mM, respectively. Then, the CoNi@CN material prepared in Example 1 was added to make its concentration in the solution about 0.05 g / L, the reaction was started, and the reaction temperature was controlled to 25°C. A certain amount of sample was taken out at regular intervals and filtered, and the filtrate was subjected to subsequent TCH concentration analysis. The removal effect under different PMS concentrations is shown in Figure 2. Figure 5 shown.

[0056] Depend on Figure 5 It can be seen that with the increase of PMS concentration, the removal efficiency of typical organic pollutants (TCH) is significantly improved.

[0057] Example 5 Effect of activated PMS on removing typical organic pollutants in water under different CoNi@CN material concentration gradients: TCH was dissolved in water to prepare multiple simulated sewage, and the TCH concentration was controlled to be 20 μM. A PMS solution with a concentration of about 100 mM was added to each group of simulated sewage and stirred to make the PMS concentration 0.75 mM. The CoNi@CN material prepared in Example 1 was then added to make its concentration in the solution 0.02 mg / L, 0.05 mg / L, 0.08 mg / L, and 0.10 mg / L, respectively. The reaction was started and the reaction temperature was controlled to 25°C. A certain amount of sample was taken out at regular intervals and filtered, and the filtrate was subjected to subsequent TCH concentration analysis. The removal effect under different PMS concentrations is shown in Figure 2. Figure 6 shown.

[0058] Depend on Figure 6 It can be seen that with the increase of CoNi@CN catalyst concentration, the removal efficiency of typical organic pollutants (TCH) is significantly improved.

[0059] Example 6 Effect of temperature on the removal of typical organic pollutants from water by CoNi@CN material activated PMS: TCH was dissolved in water to prepare multiple simulated sewage, and the TCH concentration was controlled to be 20 μM. A PMS solution with a concentration of about 100 mM was added to each group of simulated sewage and stirred to make the PMS concentration 0.75 mM. The CoNi@CN material prepared in Example 1 was then added to make its concentration in the solution 0.05 mg / L. The reaction was started and the reaction temperatures were controlled to be 15°C, 25°C, 35°C, and 45°C, respectively. A certain amount of sample was taken out at regular intervals and filtered, and the filtrate was subjected to subsequent TCH concentration analysis. The removal effect at different reaction temperatures is shown in Figure 2. Figure 7 shown.

[0060] Depend on Figure 7 It can be seen that as the temperature increases, although the removal rate of each pollutant does not increase significantly at the 25th minute, the removal rate of the pollutant (TCH) increases significantly.

[0061] Example 7 Effects of inorganic ions and NOM concentrations on the removal of typical organic pollutants from water by PMS activated by CoNi@CN materials: The influence of anions and organic matter on the degradation efficiency of TCH cannot be ignored. TCH was dissolved in water to prepare multiple simulated sewage, and the TCH concentration was controlled to be 20 μM. Cl⁻, NO3⁻, SO4²⁻ and 10 mg / L humic acid (HA) were added to each simulated sewage at a final concentration of 10 mM, respectively, and simulated sewage without anions or organic matter was used as a blank. Afterwards, a PMS solution with a concentration of about 100 mM was added to each group of simulated sewage and stirred to make the PMS concentration 0.75 mM. The CoNi@CN material prepared in Example 1 was then added to make its concentration in the solution 0.05 mg / L, the reaction was started, and the reaction temperature was controlled to 25°C. A certain amount of sample was taken out at regular intervals and filtered, and the filtrate was subjected to subsequent TCH concentration analysis. The removal effect of TCH is shown in the following figure. Figure 8 shown.

[0062] like Figure 8 The addition of NO3⁻ and SO4²⁻ had no significant effect on the degradation of TCH, with degradation rates of 95.8% and 98.4%, respectively, indicating that it can resist the interference of NO3⁻ and SO4²⁻ in the environment. In addition, HA was selected as a typical natural organic matter. HA has a significant inhibitory effect on TCH degradation. In a system containing HA, the degradation rate of TCH by CoNi@CN dropped to 87.9% within 30 minutes. This may be related to the competition between HA and organic pollutants, which consumes free radicals in the system. Cl − It also has a significant inhibitory effect on the degradation of TCH. − After 4 h, the degradation efficiency of TCH was 82.4%, which may be attributed to the− With SO4 ·− / ·OH will react and occupy the active groups of the system.

[0063] Example 8 Effect of CoNi@CN materials on the removal of typical organic pollutants in water after regeneration and recycling: The simulated wastewater that completed the degradation experiment in Experimental Example 2 was filtered through a glass fiber membrane to recover the catalyst, and then the catalyst was washed with distilled water and ethanol and dried in a vacuum drying oven at 60°C for 12 h to obtain the regenerated CoNi@CN material.

[0064] Example 2 was repeated using the regenerated CoNi@CN material, and the experimental results were as follows: Figure 9 shown.

[0065] Depend on Figure 9 It can be seen that the CoNi@CN material has good stability. After 5 times of regeneration and recycling, the removal rate of TCH degradation by CoNi@CN material in activated PMS can still reach 88.6% within 25 minutes. It can be seen that the CoNi@CN material still has a good activation effect.

[0066] The CoNi@CN material was tested using a vibrating sample magnetometer, and its saturation magnetization reached 2.96 emu / g ( Figure 10 ), which is convenient for recycling and reuse.

[0067] Example 9 XRD analysis and nitrogen isothermal adsorption-desorption experimental analysis of CoNi@CN materials before and after reaction: The CoNi@CN material before and after use in Example 2 was analyzed by XRD.

[0068] Figure 11 The main diffraction peaks of CoNi@CN are shown at approximately 44.2°, 51.5°, and 75.8°, corresponding to standard elemental nickel and cobalt (Co, PDF #15-0806; Ni, PDF #04-0850). In addition, a weak peak signal observed at 26.4° corresponds to the (002) crystal plane of graphitic carbon (graphite C, PDF #41-1487).

[0069] The BET and internal pore structure information of the CoNi@CN material before use were further detected, such as Figure 12 As shown. The specific surface area of ​​CoNi@CN is 23.47 cm 2The pore sizes of CoNi@CN are diverse, with a small peak between 0 and 10 nm, and most of the pores distributed between 40 and 80 nm. The rich pore structure can provide sufficient surface active sites for the material, thereby improving the catalytic performance of the material.

[0070] Example 10 Metal dissolution test of CoNi@CN material: In the CoNi@CN / PMS system of Example 2, the simulated wastewater samples of the degradation experiment were taken at 10 min and 25 min, respectively, and the test sample solutions were obtained after filtration. The Ni and Co elements contained therein were detected by ICP, and the results were as follows: Figure 13 The results show that within 25 minutes, the concentrations of Ni and Co dissolved from the CoNi@CN / PMS system were 0.22 mg / L and 0.29 mg / L, respectively, which are far below the regulatory threshold of 1.00 mg / L specified in the wastewater discharge standards (GB 25467-2010, GB 8978-1996).

Claims

1. A method for preparing a macrocyclic-derived cobalt-nickel supported nitrogen-doped carbon catalyst, characterized in that: The following steps are involved: (1) CB[ 7 ], cobalt salt and nickel salt are mixed and reacted in an organic solvent to obtain the complex CB[ 7 ] / CoNi; (2) The complex CB[ 7 ] / CoNi is calcined at 500-900°C under a protective atmosphere to obtain the macrocyclic-derived cobalt-nickel-supported nitrogen-doped carbon catalyst, which is denoted as CoNi@CN.

2. The preparation method according to claim 1, characterized in that In the cobalt salt and the nickel salt in step (1), the molar ratio of cobalt element to nickel element is 1:2 to 3:1, more preferably 1:

1.

3. The preparation method according to claim 1, characterized in that The cobalt salt in step (1) is cobalt acetate, and the nickel salt is nickel sulfate.

4. The preparation method according to claim 1, characterized in that The organic solvent described in step (1) is anhydrous methanol.

5. The preparation method according to claim 1, characterized in that The calcination time in step (2) is 2 to 5 hours, more preferably 2 hours.

6. The preparation method according to claim 1, characterized in that The heating rate of calcination in step (2) is 5-20°C / min, more preferably 5°C / min.

7. A macrocyclic-derived cobalt-nickel-supported nitrogen-doped carbon catalyst prepared by the preparation method according to any one of claims 1 to 6.

8. Use of the macrocyclic-derived cobalt-nickel supported nitrogen-doped carbon catalyst prepared by the preparation method according to any one of claims 1 to 6 in the degradation of organic pollutants in water.

9. The use according to claim 8, characterized in that The organic pollutants are tetracycline, sulfamethoxazole or ciprofloxacin.

10. The use according to claim 8, characterized in that The application comprises the following steps: Peroxymonosulfate is added to the water to be treated, and then the macrocyclic-derived cobalt-nickel-loaded nitrogen-doped carbon catalyst is added to the water to be treated so that the final concentration of the macrocyclic-derived cobalt-nickel-loaded nitrogen-doped carbon catalyst is 0.01-0.2 g / L, more preferably 0.05 g / L.